Pax - Pennypacker, Sara, 1951- (Balzer + Bray, 2019)
Peter rescued Pax when the fox was just a kit. And when Peter is forced to abandoned Pax after his father is called to fight in the war and Peter is sent to live with his grandfather, both Peter and Pax are heartbroken. When Peter arrives at his grandfather's home, he sets out under the cover of night to travel the 300 miles back to his home, hoping to find Pax. Meanwhile, Pax has set out on his own journey to find the boy he loves amidst the dangers of the war that rages around him and the wildness of nature he's never known.